Modeling lexical abilities of heritage language and L2 speakers of Hebrew and English in Israel and the United States: a network approach - Fridman, Clara; Livni, Adina; Bar On, Sagit; Meir, Natalia (Frontiers in Psychology, 2024)
This paper examines the productive vocabulary skills of five groups of English-Hebrew bilinguals in Israel and the USA (n=185): Hebrew-dominant heritage-English speakers, Hebrew-dominant L2-English speakers, English-dominant heritage-Hebrew speakers, and English-dominant L2-Hebrew speakers in the US and in Israel. The juxtaposition of these five groups allows us to simultaneously compare performance across dominance profiles, acquisition contexts (L2 learned in school, HL maintained at home, immigration and immersion), and countries (Israel and the United States). The results indicate clear language dominance in all the groups except Hebrew-dominant heritage-English speakers, who show highly balanced proficiency in both their languages. We then employ network modeling based on a secondary data analysis of background questionnaires to consider how each group's lexical proficiency ties in to reported input factors. The network models indicate key distinctions between the groups as a function of linguistic context, and we assess our findings in the context of recent work on quantifying the bilingual experience.